2003
DOI: 10.1111/j.1365-2915.2003.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of the Cayenne tick, Amblyomma cajennense on horses in Brazil

Abstract: The population dynamics of all stages of the Cayenne tick, Amblyomma cajennense (Fabricius) (Acari: Ixodidae) on horses was evaluated over a period of 2 years in the district of Pedro Leopoldo, State of Minas Gerais, Brazil. Every 14 days, the left side of 20 horses was brushed for collection of immature stages; counts of adults were also undertaken. Infestation by larvae was detected from April to August, whereas nymphs were observed from June to October. Infestation by adults was detected throughout the year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 21 publications
6
26
0
12
Order By: Relevance
“…Large infestations were also recorded in São Paulo and Minas Gerais (16) (22) . Horses have been considered an important link in the movement of rickettsias because they are the primary hosts for Amblyoma sculptum and serve as sentinels of human cases (22) (23) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large infestations were also recorded in São Paulo and Minas Gerais (16) (22) . Horses have been considered an important link in the movement of rickettsias because they are the primary hosts for Amblyoma sculptum and serve as sentinels of human cases (22) (23) .…”
Section: Discussionmentioning
confidence: 99%
“…Environmental information was collected during the fi eld investigation, including factors such as the presence of rural or urban/peri-urban environment, use and occupation of land, and the presence of vectors and hosts. The ticks were captured using dry ice traps and the dragging of fl annel through vegetation, and the species were identifi ed using taxonomic keys (16) (17) (18) . Ticks were also collected from horses, dogs, and from the garb of professional fi eld investigators (captors).…”
Section: Data Source and Study Variablesmentioning
confidence: 99%
“…Thus, the larval and nymph stages are mostly present in the autumn and winter, while the adult stage is observed mostly during the spring and summer (SERRA-FREIRE, 1982;LEMOS et al, 1997;OLIVEIRA et al, 2000;LABRUNA et al, 2002). Oliveira et al (2003) observed that the adult stage of A. cajennense was found more often on horses during January to March, in Minas Gerais. Souza and Serra-Freire (1992) observed intense parasitism by adults of A. cajennense on horses in the municipality of Seropédica, between October and May.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution and occurrence of A. cajennense on horses in Brazil have been studied in some regions (SOUZA; SERRA-FREIRE, 1994;LEMOS et al, 1997;HEUCHERT et al, 1999;LABRUNA et al, 2001LABRUNA et al, , 2002OLIVEIRA et al, 2003;ESTRADA-PEÑA et al, 2004). In the present study, in the microregions evaluated, high frequency of infested horses was observed, mostly with adult ticks.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos realizados em Trinidad por Smith (1975), na Argentina por Guglielmone et al (1990) e no Brasil por Souza e Serra-Freire (1992), Souza e SerraFreire (1994), Oliveira et al (2000), Labruna et al (2002) e Oliveira et al (2003) caracterizaram a dinâmica populacional de A. cajennense em vida livre e parasitária, demonstrando o desenvolvimento de apenas uma geração por ano, com picos definidos das populações de larvas, ninfas e adultos, e um maior predomínio de estádios imaturos nos meses mais frios e secos e de adultos nos meses mais quentes e chuvosos. Oliveira et al (2000) e Oliveira et al (2003) em Pedro Leopoldo, Minas Gerais, Brasil, observaram, em eqüinos e no ambiente, as maiores concentrações de larvas em abril e maio e as de ninfas no mês de julho. Outro fator importante é o tempo de permanência de cada estádio do A. cajennense no hospedeiro.…”
Section: Palavras-chaveunclassified